Islamic Education Management in the Formation of Children's Morals in Elementary Madrasahs: The Influence of Digital Media on Character Education - Nurmala Fadhilah Jaya; Hasanah Fitriya; Nur Rois; Yusuf Nur Ubaidillah; Sukarman Sukarman (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Islamic education in Madrasah Ibtidaiyah holds a foundational role in cultivating children’s moral character and spiritual values from an early age. Specific Background The rapid expansion of digital media has reshaped students’ behaviors, learning patterns, and sources of moral reference, creating tensions between classroom-based Islamic character education and unregulated digital exposure. Knowledge Gap Existing studies rarely integrate Islamic education management, character formation, and digital media challenges within a single comprehensive framework at the elementary madrasah level. Aims This study aims to examine Islamic education management in relation to children’s moral formation amid digital disruption and to formulate an adaptive management model aligned with Islamic values. Results Using a qualitative literature review, the findings identify a misalignment between moral instruction in schools and students’ digital environments, contributing to ethical vulnerability. The study formulates a Digital-Era Adaptive Islamic Education Management Model consisting of five pillars: Islamic digital moral-literacy curriculum, teachers as ethical digital role models, innovative and controlled digital learning, holistic school–parent partnerships, and authentic character-based evaluation. Novelty The novelty lies in the integrative management model that systematically combines Islamic educational principles with digital-era character challenges. Implications The model provides a strategic managerial framework for Madrasah Ibtidaiyah to harmonize technological engagement with moral and spiritual reinforcement, supporting sustainable character formation in the digital era. Highlights: Managerial misalignment exists between school moral instruction and students’ digital experiences. Five integrated strategic pillars structure adaptive management for moral development. Collaborative roles of teachers, parents, and schools are central to sustaining children’s ethics. Keywords: Islamic Education Management, Digital Media, Character Education